2006
DOI: 10.1177/08830738060210090201
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the Anterior Commissure in Moderate to Severe Pediatric Traumatic Brain Injury

Abstract: In relation to the adult brain, the immature brain might be more vulnerable to damage during and following traumatic brain injury, particularly in white-matter tracts. Given well-established evidence of corpus callosum atrophy, we hypothesized that anterior commissure volume (using quantitative magnetic resonance imaging [MRI]) in this structure would be decreased in children with moderate to severe traumatic brain injury relative to typically developing children. Second, given the purported role of the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…There have been only a few reports describing AC atrophy in certain diseases or in control subjects. [15][16][17][18]22 Sylvester 16 reported that the cross-sectional area of the AC on the sagittal section of the brain from an autopsy was significantly smaller in patients with Down syndrome than in control subjects. Although these investigators suggested AC thinning as a result of congenital malformation, it is more likely to be a result of regional brain atrophy and resultant white matter degeneration, considering the fact that 77% of patients with Down syndrome had a histopathology of AD in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been only a few reports describing AC atrophy in certain diseases or in control subjects. [15][16][17][18]22 Sylvester 16 reported that the cross-sectional area of the AC on the sagittal section of the brain from an autopsy was significantly smaller in patients with Down syndrome than in control subjects. Although these investigators suggested AC thinning as a result of congenital malformation, it is more likely to be a result of regional brain atrophy and resultant white matter degeneration, considering the fact that 77% of patients with Down syndrome had a histopathology of AD in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the medial temporal cortex, including the hippocampi, does not have direct interconnecting fibers through the AC. 15 Although atrophy of the AC has been reported in Down syndrome, 16 pediatric traumatic injury, 17 and aging in the rhesus monkey, 18 there have been no reports on its relationship with a neurodegenerative disease such as AD or other primary degenerative dementias.…”
mentioning
confidence: 99%
“…The average number of patients per study was 23 (range, 5-83 subjects). Our review identified several articles that described patient samples with extremely similar or identical demographic characteristics (eg, McCauley et al 55 and Wilde et al, 87,88,90 ) but reported either different abnormal brain regions or different analyses of DTI in relation to outcome. Thus, some of the subjects may have been reported in multiple studies published by the same group of researchers.…”
Section: Subjects With Tbimentioning
confidence: 99%
“…Children were studied exclusively in 29 of 72 articles. 4,5,[11][12][13][14]17,[19][20][21][22]25,27,42,43,55,66,75,81,[87][88][89][90][91][92][93][94]96,98 The total number of children studied across all 29 articles was 564. In addition, 20 studies included adults and children (younger than 19 years).…”
Section: Subjects With Tbimentioning
confidence: 99%
“…Speed of processing is dependent on the integrity of white matter pathways maintaining their optimal inter-connectiveness. Returning to the biomechanical deformation effects reviewed above, long-coursing axons are going to be more vulnerable, particularly interhemispheric connections, especially the corpus callosum and anterior commissure (Cecil et al, 1998;Holshouser et al, 2006;Inglese et al, 2005b;Mathias et al, 2004;Wilde et al, 2006a;Wilde et al, 2006c). Thus, neuropsychological tasks that require interhemispheric integration and0or multiple intracortical connections often show differences in the form of slowed responding, even in those with mTBI (Mathias et al, 2004) So, the hypothesis put forth in this section is that the biomechanics of brain injury simultaneously disrupt neurological function in the upper brainstem, pituitaryhypothalamic axis, medial temporal lobe, and basal forebrain concomitant with irritative injury to the vasculature and meninges, which gives rise to the symptoms observed in the post-concussive state and the neuropsychological sequela associated with such an injury.…”
Section: Functional Neuroanatomy Of Concussion and Ppcsmentioning
confidence: 99%